KOORDINASI PENERTIBAN ALAT PERAGA KAMPANYE PEMILIHAN UMUM 2024 DI KABUPATEN BANDUNG - Rudiansah, Bambang (Universitas Bina Taruna Gorontalo, 2025)
This research aims to analyze how campaign props are implemented to control general elections in Bandung Regency, because there are still many findings of campaign props installed in places where they should not be. The method used in this research uses a qualitative approach with a case study method with data collection techniques through field observations, in-depth interviews and analysis of relevant documents. The research results concluded that coordination through work guidelines, forums and conferences did not run optimally due to the large number of meetings held, while coordination through authority had results that were in line with the theory used, as well as coordination through consensus running as it should. It is also recommended that there be increased coordination in work guidelines, forums and conferences so that enforcement coordination can be carried out effectively.